Transparent memory testing based on dual address sequences - V. N. Yarmolik; I. Mrozek; V. A. Levantsevich; D. V. Demenkovets (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
An effectiveness of the application of classical non-destructive tests for testing storage devices and their main disadvantages, among which there are great time complexity and low diagnostic ability, are analysed. The concept of double address sequence 2A is defined and the examples of their formation based on counter address sequences and Gray code are provided. The basic element of non-destructive tests with the use of double address sequences is synthesized and its detecting and diagnostic abilities for different storage devices defects are explored. There are two new non-destructive tests of memory devices March_2A_1 and March_2A_2 and an estimation of their time complexity and efficiency of failure detection are given. A significantly lower time complexity of the proposed tests and their high diagnostic ability in comparison with classical non-destructive tests are shown.